Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a.(x3 - x2 -7x + 3 ) : x -3 = x2 + 2x - 1
b.( 2x4 - 3x2 - 3x3 - 2 + 6x ) : ( x2 - 2 ) = 2x2 - 3x + 1
Nhớ k cho mik nha bạn!
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{2\left(x+2\right)\left(x-1\right)}{x+2}=2x-2\)
b: \(=\dfrac{2x^3+x^2-6x^2-3x+2x+1}{2x+1}=x^2-3x+1\)
c: \(=\dfrac{x^3+2x^2-2x^2-4x+2x+4}{x+2}=x^2-2x+2\)
d: \(=\dfrac{x^2\left(x-3\right)}{x-3}=x^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)xy(x2+2y)=xy.x2+xy.2y
=x3y+2xy2
b)-4(6x2-xy)=-4.6x2+4.xy
=-24x2+4xy
c)4x[x2+6x-1/2]
=4x.x2+4x.6x-4x.1/2
=4x3+24x2-2x
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 2:
\(\left(5x+1\right)^2-\left(2xy-3\right)^2\)
\(=25x^2+10x+1-\left(2xy-3\right)^2\)
\(=25x^2+10x+1\left(4x^2y^2-12xy+9\right)\)
\(=25x^2+10x+1-4x^2y^2+12xy-9\)
\(=25x^2-4x^2y^2+10x+12xy-8\)
Bài 2:
\(\left(x-1\right)\left(x^2+x+1\right)=x^2\left(x-9\right)+2x+6\)
\(=x^3-1=x^3-9x^2+2x+6\)
\(=x^3-9x^2+2x+6=x^3-1\)
\(=x^3-9x^2+2x+6+1=x^3-1+1\)
\(=x^3-9x^2+2x+7=x^3\)
\(=x^3-9x^2+2x+7-x^3=x^3-x^3\)
\(=-9x^2+2x+7=0\)
\(\Rightarrow x=-\frac{7}{9};x=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
b: \(\dfrac{4}{x+2}+\dfrac{2}{x-2}+\dfrac{5-6x}{4-x^2}\)
\(=\dfrac{4x-8+2x+4+6x-5}{\left(x-2\right)\left(x+2\right)}=\dfrac{12x-9}{\left(x-2\right)\left(x+2\right)}\)
c: \(\dfrac{x^3+2x}{x^3+1}+\dfrac{2x}{x^2-x+1}+\dfrac{1}{x+1}\)
\(=\dfrac{x^3+2x+2x^2+2x+x^2-x+1}{\left(x+1\right)\left(x^2-x+1\right)}\)
\(=\dfrac{x^3+3x^2+3x+1}{\left(x+1\right)\left(x^2-x+1\right)}\)
\(=\dfrac{\left(x+1\right)^3}{\left(x+1\right)\left(x^2-x+1\right)}=\dfrac{x^2+2x+1}{x^2-x+1}\)
e: \(\dfrac{7}{x}-\dfrac{x}{x+6}+\dfrac{36}{x^2+6x}\)
\(=\dfrac{7x+42-x^2+36}{x\left(x+6\right)}\)
\(=\dfrac{-x^2+7x+78}{x\left(x+6\right)}\)
\(=\dfrac{-x^2+13x-6x+78}{x\left(x+6\right)}\)
\(=\dfrac{-x\left(x-13\right)-6\left(x-13\right)}{x\left(x+6\right)}\)
\(=\dfrac{\left(13-x\right)\left(x+6\right)}{x\left(x+6\right)}=\dfrac{13-x}{x}\)
a) (x-2)3-x(x+1)(x-1)+6x(x-3)
= x3-6x2+12x-8-x(x2-1)+6x2-18x
=x3-6x2+12x-8-x3+x+6x2-18x
=(x3-x3)+(-6x2+6x2)+(12x+x-18x)-8
=0+0-5x-8
=-5x-8
b xem lại đề